Evolving Plastic Responses to External and Genetic Environments. Issue 3 (March 2017) - Reuter, Max; Camus, M. Florencia; Hill, Mark S.; Ruzicka, Filip; Fowler, Kevin
Abstract : Phenotypic plasticity can mitigate adaptive trade-offs in fluctuating environments but how plasticity arises is little known. New research documents this process in a bacterial system. We highlight remarkable parallels to the evolution of sexual dimorphism and argue that their approach can aid our understanding of adaptive conflicts between the sexes.